Effect of LMS Live Forum with Deep Learning Approach on Students’ Collaborative Skills - Amarulloh, Adhitya; Riski Dwi Andrian; Muhammad Maulidun Mufid; Isna Qurrotun Aini; Wanda Ani Nizar Auliya (Epistema, 2025)
This study investigates the effect of LMS live forum activities integrated with a deep learning approach on the collaborative skills of higher education students. The research employed a one-group pretest–posttest design involving 30 undergraduate students enrolled in an Educational Technology course at a public university in Indonesia. Students participated in a series of synchronous live forum sessions in the LMS, structured using deep learning principles such as critical questioning, conceptual exploration, and collaborative problem solving. Data on collaboration skills were collected using a performance-based rubric and analyzed through descriptive statistics, the Shapiro–Wilk normality test, and a paired samples t-test. The results showed a significant increase in students’ collaborative skills after the intervention, with the mean score rising from 27.07 to 38.73. The paired t-test indicated a highly significant difference (p = .000), and the effect size (Cohen’s d = 3.70) demonstrated a very large and meaningful impact of the intervention. These findings suggest that the integration of deep learning strategies into synchronous LMS discussions fosters deeper engagement, enhances interaction quality, and supports more equitable collaborative performance among students. It is recommended that educators adopt structured deep learning–based live forum activities to strengthen collaboration competencies in digital learning environments. Future research may explore long-term effects, larger samples, and additional LMS features to optimize collaborative learning outcomes.